The year of living Danishly : uncovering the secrets of the world's happiest country - Russell, Helen, 1980- (Icon Books, 2020)
Given the opportunity of a new life in rural Jutland, the author discovered a startling statistic: Denmark, land of long dark winters, cured herring, Lego, and pastries, was the happiest place on earth. Keen to know their secrets, Helen gave herself a year to uncover the formula for Danish happiness. From childcare, education, food, and interior design to SAD and taxes, this book records a funny, poignant journey, showing us what the Danes get right, what they get wrong, and how we might all live a little more Danishly ourselves. In this new edition, published six years after the first, the author reveals how her life and family have changed, and explores how Denmark, too - or her understanding of it - has shifted. It's a messy and flawed place, she concludes - but can still be a model for a better way of living. -- Back cover.